2008
DOI: 10.1373/clinchem.2007.091975
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Simulation of the Action of Antileukemia Drugs by Measuring Apoptosis-Related mRNA in Blood

Abstract: BACKGROUND:In conventional bioassays, isolated cells are suspended in culture media, incubated in vitro for several days, and then characterized with respect to any cellular changes. In developing new molecular tests under physiological ex vivo conditions, we quantified the production of mRNAs for p21 and PUMA (p53 upregulated modulator of apoptosis), which are involved in cell cycle arrest and apoptosis, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The drug concentrations selected were based on previous studies [26, 27]. One μM of cytarabine is a clinically achievable concentration obtained in situations where a standard dose of cytarabine is administered [28].…”
Section: Resultsmentioning
confidence: 99%
“…The drug concentrations selected were based on previous studies [26, 27]. One μM of cytarabine is a clinically achievable concentration obtained in situations where a standard dose of cytarabine is administered [28].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in addition to radiation, CDKN1A and BBC3 were used as chemosensitivity markers for aclarubicin, cytarabine, bleomycin, carboplatin, cisplatin, cyclophosphamide, daunorubicin, doxorubicin, fludarabine, idarubicin, methotrexate, pirarubicin, vinblastine, vincristine, vindesine, and etoposide 15,16…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] Our group has also been focused on the quantification of DNA-damage response using a unique method we developed, 14 and found that CDKN1A and BBC3 were the most sensitive and universal marker mRNA for DNA damage in human whole blood. 15,16 In this study, this assay was used to characterize cancer susceptibility, although we do not know the results in blood samples are representative to other tissues. We chose multiple primary cancer cases as a model of cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative way, we have previously introduced a novel approach of ex vivo simulation [2][3][4][5], where drugs were directly mixed with heparinized human whole blood for only a couple of hours in test tubes, and drug-induced mRNAs were quantified using a new assay platform we developed [6]. By choosing appropriate target mRNAs, both desired function and unexpected adverse reactions can be determined.…”
Section: Introductionmentioning
confidence: 99%